Greater numbers and sizes of muscle bundles in the breast and leg muscles of broilers compared to layer chickens - Lee, Boin; Kim, Dong-Hwan; Lee, Joonbum; Cressman, Michael D.; Choi, Young Min; Lee, Kichoon (Frontiers in Physiology, 2023)
Meat-type (broiler) and egg-type (layer) chickens were bred by intensive selection over the years, resulting in more numbers and larger sizes of myofibers. Although the characteristics are important parameters in muscle growth and meat quality, muscle bundle characteristics have not been studied in poultry. Therefore, this study aimed to compare the histological characteristics of myofiber and muscle bundle in muscles between male broiler (Ross broiler breed) chickens and layer (Hy-line) chickens. Chicken muscles, pectoralis major (PM) and gastrocnemius (GM), were sampled at 49day-old and stained to analyze histological characteristics. Expectedly, body weights and weights of PM and GM muscles in 49-day-old broiler were significantly heavier than those of layers. Within the PM, broilers exhibited greater number and cross-sectional area (CSA) of myofibers than layers (3.3and 3.3-fold, respectively). The total number and CSA of PM muscle bundles were approximately 1.5 and 6.6 times greater, respectively, in broilers than layers. Moreover, broilers exhibited 2 times greater number of myofibers per bundle of PM muscle than layers. Within the GM, myofiber number and CSA were 2.3-and 2.4-fold greater, respectively, in broilers than layers. In addition, the total number of muscle bundles and bundle CSA were 2.5-and 2.1-fold greater, respectively, in broilers than those observed in the layers. The current study provides novel findings that greater muscle mass of broilers occurs by both hyperplasia and hypertrophy of muscle bundles and myofibers.